Attitudes and Practices Among Internists Concerning Genetic Testing. Issue 1 (15th May 2012) - Klitzman, Robert; Chung, Wendy; Marder, Karen; Shanmugham, Anita; Chin, Lisa J.; Stark, Meredith; Leu, Cheng‐Shiun; Appelbaum, Paul S.
Abstract: Many questions remain concerning whether, when, and how physicians order genetic tests, and what factors are involved in their decisions. We surveyed 220 internists from two academic medical centers about their utilization of genetic testing. Rates of genetic utilizations varied widely by disease. Respondents were most likely to have ordered tests for Factor V Leiden (16.8 %), followed by Breast/Ovarian Cancer (15.0 %). In the past 6 months, 65 % had counseled patients on genetic issues, 44 % had ordered genetic tests, 38.5 % had referred patients to a genetic counselor or geneticist, and 27.5 % had received ads from commercial labs for genetic testing. Only 4.5 % had tried to hide or disguise genetic information, and <2 % have had patients report genetic discrimination. Only 53.4 % knew of a geneticist/genetic counselor to whom to refer patients. Most rated their knowledge as very/somewhat poor concerning genetics (73.7 %) and guidelines for genetic testing (87.1 %). Most felt needs for more training on when to order tests (79 %), and how to counsel patients (82 %), interpret results (77.3 %), and maintain privacy (80.6 %). Physicians were more likely to have ordered a genetic test if patients inquired about genetic testing ( p  < .001), and if physicians had a geneticist/genetic counselor to whom to refer patients ( p  < .002), had referred patients to a geneticist/genetic counselor in the past 6 months, had more comfort counseling patients about testing ( p  < .019), counseled patients about genetics, larger practices ( p  < .032), fewer African‐American patients ( p  < .027), and patients who had reported genetic discrimination ( p  < .044). In a multiple logistic regression, ordering a genetic test was associated with patients inquiring about testing, having referred patients to a geneticist/genetic counselor and knowing how to order tests. These data suggest that physicians recognize their knowledge deficits, and are interested in training. These findings have important implications for future medical practice, research, and education.